Assessment of Wind Energy Potential in Golestan Province of Iran - Hashemi-Tilehnoee, Mehdi; Khaleghi, Masoud; Babayani, Dayan (International Journal of Renewable Energy Development, 2016)
Renewable energy sources are estimated to have a thriving future in many countries as well as Iran. The aim of this work is the evaluation of wind energy potentiality for the five counties of Golestan province in the northern region of Iran. A long term data source, consisting of  30 years in Gorgan, 22 years in Gonbade-e Qabus, 21 years in Maraveh Tappeh, 9 years in Aliabad, and 7 years in Bandar-e Turkaman of eight-hourly mean wind data, was adopted and analyzed. Mean wind power based on quantified data, Weibull distribution function, the relative percentage error (RPE) and wind direction between obtaining values of wind power has been considered. According to these data, it was found that the numerical values of the shape parameter and scale parameter for Golestan varied a tight range. Annual values of ‘‘k’’ ranged from 2.7 to 4.7 where it is constant in different elevation because of better performance of this method in estimating wind energy potential, while annual values of ‘‘c’’ were in the range of 2.6 m/s in 10 m and 7.6 m/s in 40 m. Wind power densities have been estimated and relatively low for large wind turbines. The consequences indicate that in some months Maraveh Tappeh and Bandar-e Turkaman has best wind energy potential, as class 2, in order to establish some small wind turbine models for the sustainable development of Golestan province. Article History: Received Sept 13, 2015; Received in revised form Dec 27, 2015; Accepted January 17, 2016; Available online How to Cite This Article: Babayani, D., Khaleghi, M. and Hashemi-Tilehnoee, M. (2016) Assessment of Wind Energy Potential in Golestan Province of Iran. Int. Journal of Renewable Energy Development, 5(1), 25-31. http://dx.doi.org/10.14710/ijred.5.1.25-31